Observations on Pingos and Permafrost Hydrology in Schuchert Dal, N. E. Greenland. - O'Brien, Robert (Meddelelser om Grønland, 1971)
The pingos of Schuchert Dal are found at intervals along the base of the eastern slope of this major North-East Greenland Valley. The morphology of the pingos is described. Together they illustrate a sequence of growth and disintegration which appears typical of open system pingos in this region. Of the six pingos examined two appear to be young, active forms, one is in an early stage of disintegration and the remainder are all relict forms in which the ice bodies have given way to lakes. Two of the latter show evidence of current reactivation. The pingos are thought to relate, hydrologically, to local secondary faults. Chemical and mass spectrometric analysis of pingo waters suggest that these are derived from deep aquifers characterised by low rates of transmission and recharge.